THE INFLUENCE OF AUGMENTED REALITY-BASED FLASHCARDS ON THE UNDERSTANDING OF THE CONCEPT OF GRADE V STUDENTS ON THE MATERIAL OF FAUNA DIVERSITY IN INDONESIA - Astri Oktavia; Ani Nur Aeni; Ali Ismail (Universitas Majalengka, 2025)
The integration of technology in learning is constantly evolving to improve student understanding. One of the challenges in teaching science in elementary schools is presenting abstract concepts, such as faunal diversity, in a way that is engaging and easy to understand. Augmented reality offers a solution by providing an immersive visual learning experience. This study aims to assess the effect of augmented reality flashcards on understanding the concept of faunal diversity in fifth grade students. This study used an experimental method with a nonequivalent control group design, students were divided into two groups, where the experimental group used augmented reality flashcards and the control group with conventional methods. Data was collected through pretest and posttest, analyzed using paired sample t-test, independent t-test, effect size, and N-Gain. The results showed a significant increase in the understanding of students who used augmented reality flashcards (Sig. 0.004 <0.05) with an effect size of 2.08 (large category). N-Gain analysis showed a higher increase in comprehension in the experimental group (0.57) compared to the control group (0.36). This finding confirms that augmented reality flashcards can be an effective learning tool for teachers in teaching abstract science concepts.